The emerging threat of human‐use antifungals in sustainable and circular agriculture schemes. Issue 6 (23rd August 2021) - Sallach, J. Brett; Thirkell, Tom J.; Field, Katie J.; Carter, Laura J.
Societal Impact Statement: Rapidly growing global populations mandate greater crop productivity despite increasingly scarce natural resources, including freshwater. The adoption of sustainable agricultural practices seek to address such issues, but an unintended consequence is the exposure of agricultural soils and associated biota to emerging contaminants including azole pharmaceutical antifungals. We show that environmentally relevant exposure to three commonly prescribed azole antifungals can reduce mycorrhizal 33 P transfer from the soil into the host plant. This suggests that exposure to azoles may have a significant impact on mycorrhizal‐mediated transfer of nutrients in soil‐plant systems. Understanding the unintended consequences of sustainable agricultural practices is needed to ensure the security and safety of future food production systems. Summary: Sustainable farming practices are increasingly necessary to meet the demands of a growing population under constraints imposed by climate change. These practices, in particular the reuse of wastewater and amending soil with wastewater derived biosolids, provide a pathway for man‐made chemicals to enter the agricultural environment. Among the chemicals commonly detected in wastewater and biosolids are pharmaceutical azole antifungals. Fungi, in particular mycorrhiza‐forming fungal symbionts of plant roots, are key drivers of nutrient cycling in the soil–plant system. As such, greater understanding of the impacts of azole antifungal exposure in agricultural systems is urgently needed. We exposed wheat ( Triticum aestivum L. cv. 'Skyfall') and arbuscular mycorrhizal fungi to environmentally relevant concentrations of three azole antifungals (clotrimazole, miconazole nitrate and fluconazole). We traced the mycorrhizal‐acquired 33 P from the soil into the host plant in contaminated versus non‐contaminated soils and found 33 P transfer from mycorrhizal fungi to host plants was reduced in soils containing antifungals. This represents a potentially major disruption to soil nutrient flows as a result of soil contamination. Our work raises the major issue of exposure of soil biota to pharmaceuticals such as azole antifungals, introduced via sustainable agricultural practices, as a potentially globally important disruptive influence on soil nutrient cycles. The impacts of these compounds on non‐target organisms, beneficial mycorrhizal fungi in particular, could have major implications on security and sustainability of future food systems. Abstract : Rapidly growing global populations mandate greater crop productivity despite increasingly scarce natural resources, including freshwater. The adoption of sustainable agricultural practices seeks to address such issues, but an unintended consequence is the exposure of agricultural soils and associated biota to emerging contaminants, including azole pharmaceutical antifungals. We show that environmentally relevant exposure to three commonly prescribed azole antifungals can reduce mycorrhizal 33 P transfer from the soil into the host plant. This suggests that exposure to azoles may have a significant impact on mycorrhizal‐mediated transfer of nutrients in soil–plant systems. Understanding the unintended consequences of sustainable agricultural practices is needed to ensure the security and safety of future food production systems.